Design and analysis of a lithium-ion battery based power supply system for electrical vehicles - Yin, Myo Myo Naing (2016)
Global Warming has become a major concern for all living things in recent decades and one of the biggest causes for global warming is carbon emission from vehicles and industries due to burning of resources like gas, fuels and coal. With this concern in mind, currently used fossil fuel vehicles should be replaced by electrically powered vehicles for the purpose of energy sustainability and environment protection. Hence, this paper discusses on a Lithium-ion battery based power supply system for electric vehicles, which focus on modelling of battery model, battery charger system and charge control. However, it is a challenge to improve efficiency and reliability of the Lithium-ion battery system because of its long charging time which limits electric cars’ performance. To deal with the challenge, factors like estimation of state of charge (SOC), proposal of precise charging algorithm, selection of suitable topology and designing of accurate control technique will be discussed in this report. Lithium-ion battery circuit is modelled as a Thevenin equivalent battery model, a DC/DC converter as a charger with a double closed-loop control circuit. Working principle and components parameters are explained in great details. The whole circuit of the system is modelled and simulated by using PowerSim (PSIM) simulation tool and results are verified and evaluated.